Toxicological and Biosafety Evaluation of Polyherbal Tea Formulation - Uwaya OD; Ehichioya S (Kwaghe International Journal of Sciences and Technology, 2026)
The safety evaluation of herbal formulations is essential for establishing their suitability for therapeutic development and use. This study assessed the acute and subacute toxicity profiles of a polyherbal tea formulated from Ageratum conyzoides, Azanza garckeana, Anthocleista djalonensis, Allium sativum, and Zingiber officinale. Acute toxicity was evaluated in mice using a modified Lorke’s method, whereas subacute toxicity was assessed in albino rats administered the formulation at doses of 0.25, 0.5, and 1.0 g/kg according to a standard protocol. No mortality occurred at 10 g/kg; therefore, the median lethal dose could not be determined. The formulation significantly increased body weight at all tested doses compared with the control group (p < .05). It reduced the spleen-to-body weight ratio (p < .05) but produced no significant changes in the relative weights of the heart, liver, kidneys, or lungs (p > .05). At 0.5 g/kg, haemoglobin concentration and platelet count decreased significantly (p < .05), whereas the remaining haematological parameters were unchanged. Alkaline phosphatase, creatinine, urea, total cholesterol, and triglyceride levels decreased significantly at all tested doses (p < .05). Aspartate aminotransferase and albumin levels decreased at 0.5 g/kg, while alanine aminotransferase decreased at 0.25 and 0.5 g/kg (p < .05); all other biochemical parameters remained stable. Histopathological examination revealed normal architecture of the kidneys, heart, lungs, and spleen, although hepatic steatosis was observed. Overall, the formulation demonstrated a high acute tolerance and limited subacute alterations at the tested doses. However, the reductions in haemoglobin and platelet counts and the presence of hepatic steatosis indicate that its biosafety profile should be interpreted cautiously. These findings provide preliminary evidence for the toxicological characterisation of the polyherbal tea and support further dose-dependent and long-term safety investigations.